FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN - PUJIATMI .; KUN ISMAWATI (Universitas Sahid Surakarta, 2018)
This study aims to determine the effect of proftability, leverage, company size, ownership structure, frm age and frm size affect the timeliness of fnancial reporting. The study was conducted at the manufacturing companies listed in Indonesia Stock Exchange in 2013, 2014 and 2015. While the sampling technique used purposive sampling method, the method of sampling based on certain criteria with a total sample of 30 companies with a total of 90 observations. Analysis model used in this research is descriptive analysis and logistic regression analysis. The results show that proftability has positive inï¬‚uence on timeliness of fnancial reports on manufacturing companies in the Indonesia Stock Exchange, Leverage a signifcant negative effect on the timeliness of fnancial reports on manufacturing companies in the Indonesia Stock Exchange, Managerial Ownership signifcantly and negatively related to timeliness fnancial reports on manufacturing companies in the Indonesia Stock Exchange, company size does not signifcantly inï¬‚uence the timeliness of fnancial reports on manufacturing companies in the Indonesia Stock Exchange, Age companies does not affect the timeliness of fnancial reports on manufacturing companies in the Indonesia Stock Exchange and Quality of CPA did not positively effect on the timeliness of fnancial reports on manufacturing companies in Indonesia Stock Exchange.